(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study examined the extent of availability and utilization of information and communication technology resources in business teacher education programme of colleges of education in Delta State, Nigeria. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. The study adopted descriptive survey design. The entire population of 114 business education lecturers in all the four colleges of education in Delta State was used for the study without sampling. Data was collected for the study through direct observation by the researcher using NCCE benchmark and administration of a validated questionnaire on the respondents. The reliability of the questionnaire was established using Cronbach Alpha formula which yielded a reliability coefficient of 0.801. Frequency count and simple percentage were used to answer research question one and mean and standard deviation were used to answer research question two. t-test statistic was used to test the hypotheses at 0.05 level of significance. The findings of the study revealed that ICT resourcesas stipulated by the benchmark of NCCE for business education programmes were not available in colleges of education in Delta State. Business educators’ rarely utilized ICT resources in business teacher education programmes in colleges of education in Delta State. The study further disclosed that business educators in colleges of education did not differ significantly in their mean ratings on the extent of utilization of ICT resources in business education programmes based on institutional ownership and location. The study concluded that the inadequacy and low level of utilization of ICT resources by business educators will negatively affected the technological competencies of business education students to succeed and curve a niche of their own in the digitalized business world. It was recommended among others that management of colleges of education should enter into partnership with ICT manufacturing organizations to assist in improving the supply of ICT resources in business education programme. This is to enhance business education students’ academic performance and boost the quality assurance indices of the programme.